Low temperature phases of strontium nitroprusside tetrahydrate (Sr[Fe(CN)5NO]·4H2O) : Refinement of the neutron structure at 60 K - Chevrier, G. (2001)
The behavior of Sr[Fe(CN)5NO]·4H2O between room temperature and 77 K has been investigated by X-ray powder diffraction (XRD), differential thermal analysis (DTA), and infrared spectroscopy (IRS).DTAputs into evidence five phase transitions—at 152.7, 174.3, 183.0, 193.0, and 199.5 K—when temperature is increased very slowly. When decreasing the temperature, XRD detects a change of space group below 153 K—from C2/m to P2/m— already reported as a result of a neutron diffraction study performed at 130 K. TheP2/mspace group remains at least down to 60 K. The structure at this temperature (monoclinic, space group P2/m, Z = 4, a = 19.765(21) A° , b = 7.540(5) A° , c = 8.384(1) A° , β = 98.87(1)◦, V = 1236(16) °A3) has been refined to a final R factor 0.077 using 687 observed structure factors. Of the two series of IR spectra obtained when cooling the sample (first series) and when heating the previously cooled sample (second series), only a feature of the first series of spectra seems to be related with the transition observed at 153 K.